The relation of stroke frequence, force and EMG in front crawl tethered swimming - Cabri, J. M. H.; Annemans, L.; Clarys, J. P.; Bollens, E.; Publie, J. (Swimming Science V, 1988)
Tethered swimming has been widely used, not only for training purposes but also in many different research areas (i.e., biomechanics, hydrodynamics, physiology, etc.). In the past 20 years, this method has been used as an alternative ''wet'' strength training method, particularly because some of the dryland training devices could not be considered as "specific to swimming" (Oarys, 1985; Olbrecht & Oarys, 1983) although they pretend to be so. With the knowledge that fully tethered swimming induces electromyographic (EMG) patterns similar to free swimming and thus may be considered specific to swimming (Bollens, Annemans, Oarys, & Vaes, 1988; Roberts, 1977) the main purpose of this study was to investigate the relationships between different stroke rates (during front crawl on a fully tethered swimming device), the forces developed, and the normalized EMG of the main propulsive arm and leg muscles using (a) raw EMG, (b)integrated EMG, and (c) linear envelope (Winter, Rau, Kadefors, Broman, & Luca, 1980). The relationship between intensity of muscle activity and actual force is described by the integrated electromyography/force ratio (IEMG/IF), for it is an expression of the efficiency of electrical activity (De Vries, 1968). Moreover, Viitasalo (1984) stated that this ratio provides a fairly good representation of the relationship benveen muscle activity and force on the one hand, and contraction velocity on the other. He concluded that from a certain amount of IEMG activity (neural input), slow (isometric) contractions may produce much higher forces in comparison with high velocity (explosive type) contractions (as in jumping). The purposes of this investigation, therefore, were to investigate the (a) influence of different stroke frequencies on the forces developed by the swimmer, (b) influence of different stroke frequencies on the IEMG/IF ratio or the relationship between stroke rate and muscular efficiency, and (c) relationship between the normalized EMG patterns and the normalized force amplitudes.